Water-based resistance training program with isolated concentric action improves physical functional capacity and muscular strength in older women - Freitas, Ana Victoria Costa; Streit, Inês Amanda; Bertoli, Josefina [UNESP]; Nascimento, Kayth Andrade; de Sá, Maria Carolina Oliveira; Teixeira, Alessandra Nunes; do Nascimento, Milenna Thamyres Alves; de Souza Bezerra, Ewertton (Springer Nature, 2021)
Background: Resistance training has proven to be an excellent method for counteracting aging physical dysfunctions. However, its application in the liquid environment is not yet fully elucidated. Aim: To investigate the effects of water-based resistance training (WBRT) with the concentric phase performed as fast as possible, compared to conventional resistance training (CRT), on physical functional capacity, muscle strength, and body composition in older women. Methods: Thirteen healthy older women participated in the WBRT and 11 in the CRT. Estimation statistics focused on the effect size of the experiment/intervention were used. We also analyzed the intervention effect based on the percentage delta between WBRT and CRT. Results: The WBRT group showed a negative large effect (d = − 0.922; p = 0.0274) for the timed up and go, and a large effect for chair rise in 30″ and the elbow flex test (d = 1.58; p = 0.0012; d = 2.8; p = 0.01) respectively. Intervention comparisons based on the delta percentage between WBRT and CRT presented an intermediate effect (d = 0.606; p = 0.157) for the stair climb, a large effect (d = 0.988; p = 0.0282) for the timed up and go, and a large negative effect [d = − 1.32 (90.0% CI − 1.92, − 0.646); p = 0.0038] for the elbow flex test. Concentric extensor-flexor peak torque (60°/s) showed an intermediate effect (d = 0.749; p = 0.0876; d = 0.65; p = 0.122 respectively). Body fat (%) demonstrated an intermediate effect (d = 0.523; p = 0.234). Conclusion: WBRT with the concentric phase performed as fast as possible was able to improve physical functional capacity and maximal knee extension strength of older women.
Keywords: Activities of daily living; Aging; Body composition; Muscle contraction; Physical exercise; Resistance training